2022
DOI: 10.1029/2022je007357
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy of a Possible Ancient Lakeshore in the Sutton Island Member of Mt. Sharp, Gale Crater, Mars, From Mastcam Multispectral Images

Abstract: The Curiosity rover on the Mars Science Laboratory mission has found extensive evidence that Gale crater once hosted a habitable lacustrine environment; however, there are remaining questions about the chemistry and duration of the lake and the nature of the climate at the time. In this study, we use Mastcam multispectral data to investigate the mineralogy of the Sutton Island member of the Murray formation, a part of the basal layers of Mt. Sharp, which consists of heterolithic mudstone and sandstone that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 90 publications
(253 reference statements)
8
9
0
Order By: Relevance
“…However, ferric smectites are most plausible based on their strong detections in orbital observations of GT (Fraeman et al., 2016) and CheMin models of up to 34 wt.% phyllosilicates in GT drill samples (Bristow, Grotzinger, et al., 2021; Thorpe et al., 2021, 2022). Similar spectral signatures have been observed in the SI member below VRR (Haber et al., 2020) and in isolated cm‐scale patches within the VRR Jm (Horgan et al., 2020). The >900 nm band was observed in all types of ROIs (dusty bedrock, DRT spots, and drill tailings) and in all three stratigraphic members in Mastcam data, but not near the GT‐Stimson contact (Figures 7 and 8).…”
Section: Vnir Reflectance Spectral Properties Of Glen Torridonsupporting
confidence: 78%
See 2 more Smart Citations
“…However, ferric smectites are most plausible based on their strong detections in orbital observations of GT (Fraeman et al., 2016) and CheMin models of up to 34 wt.% phyllosilicates in GT drill samples (Bristow, Grotzinger, et al., 2021; Thorpe et al., 2021, 2022). Similar spectral signatures have been observed in the SI member below VRR (Haber et al., 2020) and in isolated cm‐scale patches within the VRR Jm (Horgan et al., 2020). The >900 nm band was observed in all types of ROIs (dusty bedrock, DRT spots, and drill tailings) and in all three stratigraphic members in Mastcam data, but not near the GT‐Stimson contact (Figures 7 and 8).…”
Section: Vnir Reflectance Spectral Properties Of Glen Torridonsupporting
confidence: 78%
“…The clay minerals may have formed either through alteration in a lacustrine environment or laterally extensive surface weathering, whether the altered sediments were detrital or authigenic. Similar patchy clay and hematite spectral signatures in SI below VRR have been attributed to similar weathering and diagenetic processes (Haber et al, 2020). In contrast, the lack of clay spectral signatures on VRR may be due to destruction of clay minerals by late diagenetic alteration (e.g., Bristow, Grotzinger, et al, 2021;Horgan et al, 2020;.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…7c), and a spectral maximum approaching 800 nm (Fig 7b). This is consistent with Mastcam observations which suggest a significant decrease in crystalline hematite relative to the rest of the Murray formation and an increase in other iron bearing phases with band centers past the wavelength range of ChemCam (~910-930 nm) such as Fe/Mg smectite, jarosite, and akaganeite (Haber et al, 2022). This compositional change is indicative of more surface exposure and a low stand environment as described in Rapin et al, 2019. In clearly identifying this important region, principal component analysis of passive spectra has demonstrated that it is a valuable tool for gaining additional geochemical insight from ChemCam data.…”
Section: Comparison Between Spectral and Chemical Properties Of Bedro...supporting
confidence: 91%
“…PCA of ChemCam passive spectra proved useful in highlighting geochemically distinct regions of the traverse. The Blunts Point-Sutton Island transition, which contains magnesium sulfate rich targets and has been proposed as an area of low lake level by Rapin et al (2019), was found to have zero 750 nm to 840 nm spectral slope (PC4) and weak 535 nm band depth (PC2), in agreement with Mastcam data from this interval (Haber et al, 2022). The Hutton interval (sol 2750-2800) was found to be spectrally distinct from the rest of the Mt.…”
Section: Discussionsupporting
confidence: 73%